STRATEGI PEMBELAJARAN EKSPOSITORI DENGAN MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP PENINGKATAN KETERAMPILAN BERPIKIR KRITIS - Rosyidah, Aminatur; Ferdiana, Ferdiana (International Conference on Humanity Education and Society (ICHES), 2024)
Education is an important means to improve the quality of human resources in ensuring the continuity of a nation's development. Student potential needs to be developed in education to understand learning concepts, so that education can run well. In order to get active science learning results, it is not only transforming knowledge, but also trying to produce a whole human being not only cognitively but in terms of affective and psychomotor. The purpose of this study was to determine the effect of learning strategies with the TGT learning model on students' critical thinking skills. The research method used is pre-experiment using T test, one group design, pretest, posttest design. The population and research sample were students of TIPA 1A class who took Basic Science courses. Data collection techniques were carried out using test techniques, namely pre-test and post-test and data on the results of critical thinking skills obtained through essay tests carried out every meeting based on critical thinking skills indicators. The results of the study obtained an initial average value (Pretest) of 79.8 and the final value (posttest) which is 85.4 and from the results of the T test obtained Thitung 2.467 while Ttable 2.131 with a significant level of 0.05, so it can be concluded that Thitung is greater than Ttable means accepting Ho, so it can be stated that the expository strategy and TGT models is more effective.